Sense of hope affects secondary school students’ mental health: A moderated mediation model - Sun, Yajing; Yu, Haibo; Wu, Xiaoguang; Ma, Chao (Frontiers in Psychology, 2023)
Introduction The study assesses the moderated mediation effect of sense of hope on the mental health of secondary school students. Methods The Adult Dispositional Hope Scale (ADHS), Connor-Davidson Resilience Scale (CD-RISC), and the Symptom Check List 90 (SCL-90) were used to conduct a questionnaire survey on 1776 secondary school students. Results The results showed that total mental health scores of secondary school students were significantly negatively correlated with sense of hope and psychological resilience; sense of hope was significantly positively correlated with psychological resilience; sense of hope significantly and positively predicted the level of mental health of secondary school students, and psychological resilience played a mediating role in it; gender plays a moderating role in the relationship between sense of hope and psychological resilience. Discussion The study further revealed the mechanism of the effect of sense of hope on secondary school students’ mental health, and provided suggestions for cultivating positive psychological qualities and promoting the mental health development of secondary school students.